Histories of Untranslatability in South Asia: Historiography, Debates, and Problems, 1980–2010 - Krishna, Vipin (History compass, 2025)
Untranslatability is not a separate field of study in history; rather, it is a conceptual lens that captures the concerns of certain strands of scholarship which have tended to somewhat problematize connections, translations, and mediation across imperial and colonial divides. Usually, such histories have taken stock of the problematic relation shared by "universals" and "particulars," and in doing so, have sought to engage with vernacular categories and histories following the "linguistic turn" in history. South Asian postcolonial histories since the 1950s have taken stock of these issues of untranslatability with treatments of such issues reaching their zenith through the post-structuralist, Saidian, and Subaltern schools of historiography. This article surveys certain works in South Asian history and argues that untranslatability must be employed as a lens to understand the relationship that cultural translation shares with power. In examining these debates, this article revisits these concerns through a series of other concepts that have marked the historiography of the problem in recent times, namely continuity, conciliation, and commensurability, before reconsidering whether untranslatability can still serve as a meaningful historiographical tool, and how it has begun to figure as one in newer works.